2016
DOI: 10.1172/jci83942
|View full text |Cite
|
Sign up to set email alerts
|

Paracellular epithelial sodium transport maximizes energy efficiency in the kidney

Abstract: Efficient oxygen utilization in the kidney may be supported by paracellular epithelial transport, a form of passive diffusion that is driven by preexisting transepithelial electrochemical gradients. Claudins are tight-junction transmembrane proteins that act as paracellular ion channels in epithelial cells. In the proximal tubule (PT) of the kidney, claudin-2 mediates paracellular sodium reabsorption. Here, we used murine models to investigate the role of claudin-2 in maintaining energy efficiency in the kidne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
92
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(97 citation statements)
references
References 64 publications
4
92
0
1
Order By: Relevance
“…Organ-specific features of tight junction-dependent barrier function have been studied in the lungs (Schlingmann et al 2016), kidneys (Pei et al 2016), and gastrointestinal tract (Wada et al 2013), but have been analyzed in greatest detail in the context of gastrointestinal disease (Clayburgh et al 2005; Heller et al 2005; Weber et al 2008, 2010; Su et al 2009; Marchiando et al 2010a). In vitro, reductionist models of barrier loss in inflammatory bowel disease (IBD) include epithelial responses to exogenous tumor necrosis factor-伪 (TNF) and interleukin-13 (IL-13), which have each been implicated in Crohn鈥檚 disease and ulcerative colitis, the two forms of IBD.…”
Section: Tumor Necrosis Factor-mediated Regulation Of Tight Junction mentioning
confidence: 99%
“…Organ-specific features of tight junction-dependent barrier function have been studied in the lungs (Schlingmann et al 2016), kidneys (Pei et al 2016), and gastrointestinal tract (Wada et al 2013), but have been analyzed in greatest detail in the context of gastrointestinal disease (Clayburgh et al 2005; Heller et al 2005; Weber et al 2008, 2010; Su et al 2009; Marchiando et al 2010a). In vitro, reductionist models of barrier loss in inflammatory bowel disease (IBD) include epithelial responses to exogenous tumor necrosis factor-伪 (TNF) and interleukin-13 (IL-13), which have each been implicated in Crohn鈥檚 disease and ulcerative colitis, the two forms of IBD.…”
Section: Tumor Necrosis Factor-mediated Regulation Of Tight Junction mentioning
confidence: 99%
“…The paracellular movement of water through the channel forming claudin-2 in choroidal cells may also explain, at least partially, why knocking out aquaporin-1 in mouse decreased CSF secretion only by 35% [103]. The basis for having both a transcellular water pathway through aquaporin and a paracellular water pathway through claudin-2 could be to provide an energy saving mechanism, as shown in the renal proximal tubule [106].…”
Section: Paracellular Barrier Properties Of the Choroid Plexus Epithementioning
confidence: 99%
“…6 We found that claudin-2 null mice have similar rates of renal tubule Na C reabsorption (T Na ) to wild-type mice, but that the rate of renal oxygen consumption (QO 2 ) is substantially higher (Fig. 2).…”
Section: Role Of Claudin-2 In Energy Saving By the Kidneymentioning
confidence: 72%
“…In our studies we found that this was because the defect in proximal paracellular Na C reabsorption is fully compensated by increased Na C reabsorption further downstream in a tubule segment called the thick ascending limb of Henle's loop. 6 This raised the question of what is the true role of paracellular transport in the proximal tubule. We propose that paracellular transport exists in the proximal tubule because it allows transepithelial transport to be accomplished in a more energy-efficient manner.…”
mentioning
confidence: 99%